The characterisation of a recent syphilis outbreak in Sheffield, UK, and an evaluation of contact tracing as a method of control. Issue 3 (6th December 2006) - Singh, Selena; Bell, Gill; Talbot, Martin
Abstract : Objective: To explore the factors around and the success of contact-tracing in a recent major outbreak of infectious syphilis in Sheffield, and to evaluate the effectiveness of it, our hitherto standard strategy of control. Method: Retrospective chart review Results: Over a period of 18 months, an outbreak of 21 cases was, on closer inspection, the result of several, discrete "micro" outbreaks in different groups. Two major patterns emerged, a relatively straightforward and more accessible cluster in heterosexual persons (a "spread" network), and more sporadic, "starburst" networks in men who have sex with men. Conclusion: Our traditional method of control, contact-tracing, was seen to be most effective in the spread network in heterosexuals. In the face of an apparent outbreak, clinicians should explore the nature and parameters of their local epidemic and engage a mixture of control methods. These may include, but not excusively so, contact-tracing to interrupt transmission by case-finding and by treatment.